Dietary Fiber's Effect on High Sensitivity C-reactive Protein Serum in Sedentary Workers - Livia Kurniati Saputra; Dian Novita Chandra; Ninik Mudjihartini (Indonesian Nutrition Association, 2021)
Low grade inflammation has been recognized of being involved in the pathogenesis of chronic disease pandemic. Individual lifestyle plays a major role in the development of low grade inflammation. Sedentary workers are at risk of low grade inflammation due to the nature of their work. Dietary habit also contributes to inflammatory status in the body. Dietary fiber intake indirectly affects the immune system. It has been hypothesized that fiber has anti-inflammatory effects, both body weight-related and body weight-unrelated This review will focus more on body weight-unrelated anti-inflammatory effect of fiber, especially through fiberâ€™s fermentation metabolites, the short chain fatty acid (SCFA). Its anti-inflammatory effect can be seen by monitoring a biomarker of inflammation in the body, the high sensitivity C-reactive protein (hsCRP). This reviewâ€™s objective is to cover the mechanisms and role of dietary fiber intake on serum hsCRP level as a marker of low grade inflammation on sedentary workers.Â